Hormonal make up of stagheads of Brassica infected by Albugo candida - S.S. SOKHI, RAVJIT K. KHANGURA* and (Indian Phytopathology, 2002)
The stagheads (malformed inflorescences) in Brassica juncea vars. RL-1359, RLM-619 and Brassica campestris var. TL-15 caused by Albugo Candida (Pers. ex Lev.) Kuntze showed lower levels of indole-3-acetic acid and higher levels of gibberellic acid, zeatin and abscisic acid as compared with healthy inflorescences.